Artificial Intelligence and Newsgames in Journalism: Proposals and ideas from the case study of three projects - Tejedor, Santiago (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Technology and emerging user profiles have opened up interesting scenarios for the ideation of new journalistic and communicative formats. Artificial Intelligence (AI) and gamification proposals boost the creation of informative pieces that exploit the possibilities of cyberspace and, at the same time, adapt to new audiences. Based on three research projects and using a methodology based on case studies, the study highlights the fact that these technological developments make it possible to renew the usual formats of journalism and concludes that they have great informative, educational and awareness-raising potential.